Body mass index and the risk of head and neck cancer in the Chinese population. (June 2019) - Chen, Yuji; Lee, Yuan-Chin Amy; Li, Shuang; Li, Qian; Chen, Chien-Jen; Hsu, Wan-Lun; Lou, Pen-Jen; Zhu, Cairong; Pan, Jian; Shen, Hongbing; Ma, Hongxia; Cai, Lin; et al.
Highlights: Low body mass index, even at age 20, was associated with a higher risk of HNC. Being obese was associated with a lower risk of HNC. BMI loss was also an important risk factor for HNC. Abstract: Objective: To investigate potential associations between body mass index (BMI) and head and neck cancer (HNC) risk in an East Asian population. Methods: We conducted a hospital-based multicenter case-control study in East Asia including 921 cases and 806 controls. We estimated the odds ratios (ORs) and 95% confidence intervals (95% CI) for HNC risks by using logistic regression, adjusting on potential confounders. Results: Compared to normal BMI at interview (18.5–<25 kg/m 2 ), being underweight (BMI < 18.5 kg/m 2 ) was associated with a higher HNC risk (OR = 2.71, 95% CI  1.40–5.26). Additionally, obesity (BMI > 30 kg/m 2 ) was associated with a lower HNC risk (OR = 0.30, 95% CI  0.16–0.57). Being underweight at age 20 was also associated with an increased risk of HNC. However, being underweight at 5 years or 2 years before interview was not associated with a higher risk of HNC. Conclusion: We observed an inverse association between BMI and HNC risk, which is consistent with previous studies in other geographic regions. Being underweight at age 20 was also associated with a higher risk of HNC, suggesting that reverse causality was not the main source of the association.